Basic mechanisms of spinal cord injury (SCI) - Hall, Edward D. (Henry Stewart Talks, 2012)
Spinal Cord Injury, Outcomes and epidemiology, Prevalence of blunt cord injury vs. transection, Primary vs. secondary injury, Importance of axonal and myelin sparing, Molecular mechanisms of secondary injury, Success with antioxidant therapies, Future neuroprotective vs. neurorestorative treatments